2015
DOI: 10.1007/s00520-015-2773-y
|View full text |Cite
|
Sign up to set email alerts
|

Low-level laser therapy alleviates mechanical and cold allodynia induced by oxaliplatin administration in rats

Abstract: The findings of this study support LLLT as a potential treatment for oxaliplatin-induced neuropathy. Moreover, our findings suggest that SP, TRPM8, and NGF proteins in the superficial dorsal horn and DRG may be involved in an antiallodynic effect for LLLT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…The results showed that repeated application of LD-LLLT significantly reduced the oxaliplatininduced cold and mechanical allodynia. These findings indicate that LD-LLLT might be a potential treatment option for CIPN [62].…”
Section: Lllt In the Management Of Cipnmentioning
confidence: 68%
“…The results showed that repeated application of LD-LLLT significantly reduced the oxaliplatininduced cold and mechanical allodynia. These findings indicate that LD-LLLT might be a potential treatment option for CIPN [62].…”
Section: Lllt In the Management Of Cipnmentioning
confidence: 68%
“…It was possible to evidence the lack of clinical trials evaluating the effect of LLLT on CTS, although there are several experimental studies with this resource used as a form of treatment in peripheral nerve injury, [22][23][24][25][26][27][28][29][30][31][32] as well as projects 33 demonstrating the interest in this form of therapy for this disease, thus denoting the importance of new studies. However, this small number of studies can also be justified due to the fact that the search is performed in only two databases and in only two languages, being one of the limitations of this study.…”
Section: Resultsmentioning
confidence: 99%
“…[ 22 ] Although there are different types of nerve fibers with different speeds, the cooling might decrease the velocity of each one to some proportions. [ 23 ] Moreover, the mild pressure of the ice popsicle itself may produce other stimuli and reduce the pain. In other aspects, the local cooling causes vasoconstriction and reduces the tissue metabolism, the inflow of inflammatory mediators during penetration of needle.…”
Section: Resultsmentioning
confidence: 99%